Provision of Counseling and Socialization Services to Reduce Anxiety of Game Addiction and Nomophobia to Adolescents in Pabuaran Village Gn. Sindur - Veno Dwi Krisnanda; Deasy Dwi Cahyaningtyas Arifin; Suhfi Albab (Jurnal PkM (Pengabdian kepada Masyarakat), 2023)
Addiction to games is a condition in which a person experiences excessive discomfort, anxiety, anxiety, or sadness because they cannot interact with their mobile device. This can be considered as a result of excessive smartphone use and has a negative impact on the individual. Nomophobia is also one of the effects of this addiction, in which a person feels anxious or afraid when they are away from their smartphone. The level of discomfort, anxiety, anxiety, or sadness in people who experience game addiction has exceeded normal limits and can be considered as addictive behavior. It is important for us to be aware of the negative impacts that may arise from dependence on smartphones and games. Efforts need to be made to limit smartphone use wisely, maintaining a balance between digital life and real life. In this way, we can avoid the trap of game addiction and maintain a more balanced and fulfilling quality of life.